IFN-Aging: Coupling Aging With Interferon Response - Cao, Wei (Frontiers in Aging, 2022)
Chronic inflammation affects many diseases and conditions, including aging. Interferons are a part of the immune defense against viral infections. Paradoxically, various aging tissues and organs from mammalian hosts perpetually accumulate changes brought by interferon pathway activation. Here I connote the mechanisms behind this phenomenon and discuss its implications in age-related pathology.